2020
DOI: 10.31703/gssr.2020(v-ii).15
|View full text |Cite
|
Sign up to set email alerts
|

Portrayal of CPEC in Leading Pakistani Urdu Newspapers

Abstract: The research study was conducted to find out the emergence of CPEC in Daily Urdu Express newspaper and Daily Urdu Jang newspaper, factors of overall positive and negative emergence of CPEC. Quantitative method was used, and the content analysis was applied to the sample of two leading dailies Urdu newspapers of Pakistan; Express and Jang. Sample of entire year of 2016 was taken for this account. The results indicated that 88.9% of the total news about CPEC published in Daily express were positive and 11.1% neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…According to Afzaal et al (2019), Pakistani print media portrays China and Pakistan as having cordial ties. The results of this study support the study by Nazir et al (2019), which asserts that the CPEC was framed favourably in the areas of infrastructure, security, growth, employment, education, energy, and business. The results also provide credence to studies by Usman et al (2020) & Shah et al (2020 who painted a favourable picture of the CPEC in terms of development, politics, social issues, economics, and strategic considerations.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to Afzaal et al (2019), Pakistani print media portrays China and Pakistan as having cordial ties. The results of this study support the study by Nazir et al (2019), which asserts that the CPEC was framed favourably in the areas of infrastructure, security, growth, employment, education, energy, and business. The results also provide credence to studies by Usman et al (2020) & Shah et al (2020 who painted a favourable picture of the CPEC in terms of development, politics, social issues, economics, and strategic considerations.…”
Section: Introductionsupporting
confidence: 87%
“…Their qualitative analysis found that China and Pakistan are presented in friendly relations in the print media of Pakistan. Print media also found to be playing same role in the research study by Nazir et al (2019). Their quantitative analysis showed that Urdu newspapers of Pakistan are portraying the CPEC in a positive way.…”
Section: Introductionmentioning
confidence: 73%
“…The local print media, which is mainly in the local language of Urdu, has a very strong impact on ordinary citizens, especially in rural under-developed areas of Pakistan. Investigating the impact of the Urdu newspaper on the CPEC project, Nazir [54] found that the Urdu newspaper offers a positive portrayal of CPEC, especially in terms of security in the region, peach initiatives, China-Pakistan relations, and the development of infrastructure. Such newspapers are read throughout the country daily, which gives a projection of the CPEC to local residents.…”
Section: Perceived Media Impactmentioning
confidence: 99%
“…The findings of this study suggest that both the Countries` Newspapers highlighted mostly the positive aspects of the project instead of negative to the residence of both countries and framed their news stories in way that encourage stakeholders in acquiring maximum reimbursements from the project (Nazir et al, 2018). In total, this study would contribute to the international relations, foreign policy, policy studies, and security studies generally and journalism-related studies particularly.…”
Section: H5mentioning
confidence: 76%
“…The Chinese newspapers have the worldwide readership, so they should concentrate on CPEC in the news stories as they frame BRI, which will create awareness on a global level about the significance of CPEC. Nazir, Ali and Farooq (2018) carried out a Comparative study under the title `Emergence of CPEC in the Pakistani Leading newspapers` they observed the overall positive and negative factors in two leading Urdu newspapers of Pakistan regarding CPEC using a quantitative method applying content analysis to determine the nature of the entire 2016 news stories in both the newspapers, their finding concluded that 88.9% news stories were framed positively and only 11.1% stories were framed negatively, they debated that media is playing its effective role in portraying the positive image of project, positive statement of the government and authorities are more highlighted in both the newspapers, therefore resulting in eradication the formal gap between the authorities and the stakeholders and creating the bridge between them.…”
Section: H5mentioning
confidence: 99%